PENGARUH DEFISIT EVAPOTRANSPIRASI DALAM REGULATED DEFICIT IRRIGATION (RDI) PADA KEDELAI (Glycine Max[L.] Merr.) - R. A.Bustomi Rosadi; Ridwan .; Nugroho Haryono; Omi Istiawati (PERTETA, 2006)
ABSTRACT The objective of this research was to investigate the effect of deficit evapotranspiration in regulated deficit irrigation (RDI) on soybean. This research was conducted on an experimental farm under plastic house of Lampung Polytechnique from Augustus to Nupember 2004. The deficit evapotranspiration treatment rates were ET1, (1.0XETC), ET2 (0.8XETC), ET4 (0.4XETC) and ET5 (0.2XETC). Arranged in a randomized block design with four reflications. Irrigation was given at two days interval. The regulated deficit irrigation (RDI) treatment just at vegetative period and its treatmens were stopped at the beginning of flowering phase and afterward the treatmens were watered at 1. 0xetc. The soil water content was monitored by porous blocks. The result showed that soybean plant strated to be stressed at week II with qc = 224.03 %, and Ks = 0.60 when watered at o.6xetc. the optimum yield of soybean plant (31.04 g/plant/0 with CWR=200.39 mm was reached by deficit irrigation at 0.8xetc during the vegetative period. Keywords: ultisol, regulated deficit irrigation, soybean, water stress coefficent